A rapid protocol to test genetic purity of pearl millet (Pennisetum glaucum) genotypes - KUMAR, M B ARUN; SHERRY, R; VARIER, ANURADHA (The Indian Journal of Agricultural Sciences, 2011)
A new protocol has been standardized for analyzing seed esterases extracted from single seeds of pearl millet, which will be helpful in testing genetic purity of seed lot and for establishing the uniformity and stability of new cultivars during Distinctness, Uniformity and stability testing. Extraction ofcrude enzymes from single dry seed in 60Jll of 100 m M Tris-Hel (pH 7.5) buffer and then leaving the contents for 4 hr at 4°C before centrifugation (at 14000 rpm for 15 minutes at 4°C) gave the similar electrophoretic banding pattern as that ofesterases extracted from 10 bulked seeds.